2020
DOI: 10.1093/geront/gnz157
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework to Guide Intervention Research Across the Trajectory of Dementia Caregiving

Abstract: This article presents a comprehensive conceptual framework designed to foster research in the changing needs of caregivers and persons with dementia as they move through their illness trajectory. It builds on prior theoretical models and intervention literature in the field, while at the same time addressing notable gaps including inadequate attention to cultural issues; lack of longitudinal research; focus on primary caregivers, almost to the exclusion of the person with dementia and other family members; lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 66 publications
1
47
0
Order By: Relevance
“…Previous literature has found that older adults with mild or minimal cognitive impairment are more likely to lose IADL independence compared to those with no impairments (Dodge et al, 2005) and that IADL restrictions in MCI predicted future dementia (Gold, 2012). As functional dependency predicts dementia and is accelerated by progression of cognitive impairment, this study aligns with past studies calling for identification of precursors and for early and timely interventions to older Mexican Americans living with mild cognitive impairment (Gallagher-Thompson et al, 2020). This study also supports previous studies showing that multiple domains of cognitive impairment, especially domains of memory and executive function, predicted IADL dependence, with executive functioning being the strongest predictor (Mansbach & Mace, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Previous literature has found that older adults with mild or minimal cognitive impairment are more likely to lose IADL independence compared to those with no impairments (Dodge et al, 2005) and that IADL restrictions in MCI predicted future dementia (Gold, 2012). As functional dependency predicts dementia and is accelerated by progression of cognitive impairment, this study aligns with past studies calling for identification of precursors and for early and timely interventions to older Mexican Americans living with mild cognitive impairment (Gallagher-Thompson et al, 2020). This study also supports previous studies showing that multiple domains of cognitive impairment, especially domains of memory and executive function, predicted IADL dependence, with executive functioning being the strongest predictor (Mansbach & Mace, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…However, extant theoretical models have not taken sufficient account of how caregiving distress differs from one individual to another and changes over time. In other words, we can expect individuals to respond differently to different interventions, depending on their needs and unique situations along the trajectory of the caregiving career (Gallagher-Thompson et al, 2019). Unfortunately, there has been a tendency to assume that “one size fits all.” By showing what interventions work for which outcomes, our findings may facilitate matching caregivers’ needs to interventions.…”
Section: Concluding Comments and Future Research Directionsmentioning
confidence: 99%
“…However, less is known about how caregivers' mental health is associated with care recipients' cognitive function 4 . People with dementia are characterized by progressive declines in cognitive function that typically begin as mild but then progress variably to a point of requiring intensive care 5 . Given recurring daily routines and exchanges between caregivers and recipients, the stress process model posits that health outcomes develop with continuous and cumulative exposure to stressors 6 .…”
Section: Introductionmentioning
confidence: 99%